1999
DOI: 10.1139/g99-072
|View full text |Cite
|
Sign up to set email alerts
|

Geographic dimorphism of the wild silkworm, Bombyx mandarina, in the chromosome number and the occurrence of a retroposon-like insertion in the arylphorin gene

Abstract: Individuals of the wild silkworm, Bombyx mandarina, collected in South Korea (Taegu City) and Japan (Tsushima Islands and Fukuoka City) had the chromosome number of 2n = 54, while those collected in China (Hangzhou City) had the chromosome number of 2n = 56. Analysis by PCR (polymerase chain reaction) showed that the 66-bp-long retroposon-like insertion known in the arylphorin gene was present in the B. mandarina specimens with 2n = 54, but not in those with 2n = 56. Thus, dimorphism in the chromosome number c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 8 publications
2
13
0
4
Order By: Relevance
“…It should be noted that ChBm and B. mori have the same number of chromosomes per haploid genome. A geographical survey and early work on ribosomal gene structure of the two karyotypic forms of wild silkworms suggested that the separation between the two types occurred north of the Korean Strait [32,33] . One recent study on interspecific hybrids of B. mori and the JaBm revealed that the M-chromosome of JaBm corresponds to two chromosomes of B. mori [9] Because the two types of wild silkworms are difficult to distin (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that ChBm and B. mori have the same number of chromosomes per haploid genome. A geographical survey and early work on ribosomal gene structure of the two karyotypic forms of wild silkworms suggested that the separation between the two types occurred north of the Korean Strait [32,33] . One recent study on interspecific hybrids of B. mori and the JaBm revealed that the M-chromosome of JaBm corresponds to two chromosomes of B. mori [9] Because the two types of wild silkworms are difficult to distin (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, higher mutation rates are predicted for the Z chromosomes or the autosomes compared with the W chromosome because more cell divisions are required for spermatogenesis compared with oogenesis. The nucleotide sequences of the autosomes of B. mori , however, show high similarity with those of B. mandarina (Kusuda et al ., 1986; Nakamura et al ., 1999; Rodakis & Lecanidou, 1992). Therefore, estimating the time of divergence of the two Bombyx species by comparing the nucleotide sequences of their autosomes or Z chromosomes is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Bombyx mandarina Moore is presumed to be the wild ancestor of B. mori because fertile hybrid progeny are produced from a cross between these two species (Nakamura et al 1999). Bombyx mandarina inhabits China, Korea, Japan, and far eastern Russia and is independent of humans, whereas the domesticated B. mori can no longer survive in nature.…”
Section: Discussionmentioning
confidence: 99%